Development of Azo-Based Turn-On Chemical Array System for Hydrazine Detection with Fluorescence Pattern Analysis - Shin, Min Chul; Lee, Youngjun; Park, Seung Bum; Kim, Eunha (ACS Omega, 2019)
A facile turn-on chemical sensor array was developed for hydrazine detection by means of fluorescence pattern recognition. Taking advantage of the unique properties of the azo group, four different fluorogenic probes, Seoul-Fluor (SF)-Azo 01-04, were designed and prepared. SF-Azo 01-04 displayed fluorescence enhancement of up to 800-fold upon reaction with hydrazine, and all probes exhibited excellent selectivity in the presence of various anions and nucleophiles. By employing the probes in a cellulose paper-based array system, the hydrazine concentration was successfully determined by monitoring the change in fluorescent patterns.